Advanced practice nursing roles in Arab countries in the Eastern Mediterranean region: a scoping review protocol. Issue 4 (1st April 2021) - Almukhaini, Salma; Martin-Misener, Ruth; Weeks, Lori E.; Macdonald, Marilyn; Hussain, Haifaa; Macdonald, Danielle; Al-Ismaili, Zeyana; Al-Fahdi, Noora; Rothfus, Melissa A.
ABSTRACT: Objective: The objective of this review is to explore and synthesize evidence regarding the advanced practice nursing roles in Arab countries in the Eastern Mediterranean region. Introduction: Many countries have witnessed an increase in the number and types of advanced practice nursing roles. The literature has documented many positive patient outcomes associated with care provided by advanced practice nurses. The International Council of Nurses claims that advanced practice nursing is country-sensitive. Despite the availability of international literature that explores advanced practice nursing roles globally, little attention has been given to advanced practice nursing roles in Arab countries in the Eastern Mediterranean region. Inclusion criteria: This review will consider studies related to advanced practice nursing roles, such as the historical development, role title, regulations, entry level education, role implementation, and outcomes, in Arab countries in the Eastern Mediterranean region. Methods: A comprehensive systematic search will be completed for both published and non-published literature using CINAHL (EBSCO), PubMed (NLM), PsycINFO, Embase (Elsevier), Nursing and Allied Health (ProQuest), Scopus (Elsevier), and websites such as Google Scholar, ProQuest Dissertations and Theses, International Council of Nurses' Nurse Practitioner/Advanced Practice Nursing Network, World Health Organization regional office for the Eastern Mediterranean, and nursing associations and ministries of health in Arab countries. The search will include literature published in Arabic and English, from the inception of databases to present.